The Future of Dental Materials: Biocompatible and Sustainable Polymers - Bharti Raina, Dinesh Deshwal, Nitesh Singh, Ravi Kumar Deshwal, Sumira Malik, Sarvesh Rustagi (Journal of Neonatal Surgery, 2025)
Extensive research into creating materials produced from renewable sources has been prompted by the depletion of petroleum-based resources, the detrimental effects of industrial processes, and growing environmental awareness. Dental materials research and development are essential to clinical dentistry. Sustainable, biodegradable, and environmentally friendly substitutes for traditional polymers are becoming more and more popular due to growing environmental awareness and legal requirements. The use of biopolymers in dentistry is examined in this review along with a comparison to traditional polymers. Epoxy resin, one of the most popular resins in dental materials, is given special attention. Its function as an epoxy resin-based sealer is examined, as well as its thermal, chemico-physical, biocompatible, and viscoelastic characteristics. Even while newly mixed epoxy resin is known for its superior sealing and physical qualities, it has strong cytotoxic effects on osteoblasts. Since biopolymers produced from sustainable sources have shown improved biomechanical qualities, this review emphasizes the necessity of creating environmentally friendly epoxy resins from renewable resources in order to lessen these consequences.